ANTIFUNGAL POTENTIAL OF BIOACTIVE COMPOUNDS OF BIOWASTE FRUIT PEEL OF PUNICA GRANATUM AGAINST PATHOGENIC FUNGI - RICHA SAXENA; RICHA SHARMA; GAJANAND SHARMA; PANKAJ SAXENA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The worldwide attention in scientific examination is to discover the herbal and natural medicine, as a result provided that them for pharmacological production and food security without any harmful property on human healthiness. Punica granatum plant is rich in medicinal properties and has high bioavailability. Pomegranate fruit has a biowaste fruit peel with potential therapeutic applications. Pomegranate biowaste fruit peel extract and fractions are most potential due to their high efficiency. The earlier study confirmed the significant antioxidant and antibacterial properties of pomegranate coating as herbal food additives. This paper highlights the relevant and recent antifungal applications against pathogenic fungi established in the prime alteration of biowaste fruit peel of P. granatum. Antifungal activity of the ethanolic extract and fractions of selected plant part were carried out by disk diffusion method against selected plant pathogenic fungi. The results showed that selected fractions of P. granatum biowaste fruit peel (PG II) have great potential as antifungal compounds against Colletotrichum gloeosporiodes (22 mm) than Rhizoctonia solani. The MIC value of both selected fungi was evaluated by agar dilution method varied as of 0.1 µgmL-1 to 2 mgmL-1. Therefore, the current study aims to account the PG II fraction of biowaste fruit peel of P. granatum is a major source of polyphenolic complexes. Although, the present study recommended the pomegranate biowaste fruit peel that can place as a relatively more precious plant source of herbal secondary metabolites for rising novel efficient food-pharma constituents with encouraging human being fitness.